Pattern of caries and gingivitis in a selected population of schoolchildren aged 9 to 11 years - Safii, S.H.; Shoaib, L.A.; Awang, H. (Penerbit Universiti Kebangsaan Malaysia, 2013)
The objectives of this study were to determine the prevalence of caries and gingivitis in a selected population of schoolchildren and to examine the relationship between prevalence of the diseases with their oral health behaviours. A total of 39 subjects, aged nine to 11 years, from 147 schoolchildren of a private school in Selangor, Malaysia were examined by two calibrated examiners trained in their own field. The subjects were interviewed using structured questionnaires. Erupted first permanent molars and permanent anterior teeth were examined. Dental caries, Plaque Score and Gingival Index were recorded. Descriptive statistics using frequency distribution were used to analyse the data. Forty-one percent of the subjects presented with more than 75 of total plaque accumulation. Prevalence of caries and gingivitis for the subject population was 18.0 and 31.0, respectively. Caries was found on both the smooth (buccal/lingual/palatal) and occlusal surfaces. Gingivitis, diagnosed around 31.6 of teeth, was found more on the incisors (16.9) than molars (14.7). A relatively higher distribution of gingivitis was found on labial aspect of the incisors (5.5) and palatal/lingual aspect of the molars (4.7). The prevalence of caries and gingivitis in this selected population was low. Certain dentition sites were more susceptible to dental caries and gingivitis. Good toothbrushing habits and regular visits to the dentists do not guarantee the efficacy of plaque removal.